1995
DOI: 10.1192/bjp.167.4.456
|View full text |Cite
|
Sign up to set email alerts
|

Social Deprivation and Psychiatric Admission Rates Among Different Diagnostic Groups

Abstract: The association between psychiatric admission rates and measures of deprivation varies considerably with diagnosis. Measures of social deprivation may indicate need for services for patients with psychotic disorders; admission rates for non-psychotic illnesses may reflect the availability of beds rather than need.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
1
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 12 publications
6
36
1
1
Order By: Relevance
“…The primacy of deprivation as the main area contextual influence on psychiatric outcomes is challenged firstly by findings that area deprivation is more relevant to explaining variations in some psychiatric conditions than others; for example, Peen and Dekker (2001) find area deprivation to have relatively weak role in explaining variability in affective psychosis as compared to schizophrenia, while Harrison et al (1995) find a negative impact of deprivation on hospitalisations for neurotic disorders. The second main finding against the primacy of deprivation as the main contextual influence on population psychiatric morbidity is the widespread evidence that community cohesion, albeit variously conceptualized and measured, affects population mental health and suicide rates.…”
Section: Discussionmentioning
confidence: 96%
“…The primacy of deprivation as the main area contextual influence on psychiatric outcomes is challenged firstly by findings that area deprivation is more relevant to explaining variations in some psychiatric conditions than others; for example, Peen and Dekker (2001) find area deprivation to have relatively weak role in explaining variability in affective psychosis as compared to schizophrenia, while Harrison et al (1995) find a negative impact of deprivation on hospitalisations for neurotic disorders. The second main finding against the primacy of deprivation as the main contextual influence on population psychiatric morbidity is the widespread evidence that community cohesion, albeit variously conceptualized and measured, affects population mental health and suicide rates.…”
Section: Discussionmentioning
confidence: 96%
“…With growing distance from the facility, the hospitalization risks in the addiction-psychiatric field seem to decrease. From this it can be concluded that spatial availability of the facilities plays an important role in the use of psychiatric inpatient services by patients with alcohol abuse [4,16].…”
Section: Discussionmentioning
confidence: 99%
“…Without going into extensive detail, some key proportions were collected in previous studies (Harrison, Barrow, & Creed, 1995;Harvey, 1996;Meltzer et al, 1995). Estimates for London showed an estimated prevalence rate for psychosis of 0.4%, while this can reach 2% in some inner-city areas.…”
Section: Mental Health Care Planningmentioning
confidence: 99%